EKSISTENSI BISNIS TEMBAKAU DI MASA PANDEMI COVID-19 DI UD AL-MUSTHOFA - Neli Hajar; Supriyanto Supriyanto; Ahmad Syaifudin (JURNAL ILMIAH EDUNOMIKA, 2021)
With the development of time in establishing a business, of course there are many challenges that must be faced and anticipated, one of which is competition. Business competition here, companies or business people are required to be more intensive in facing increasingly fierce competition. Business competition faced by entrepreneurs or business people does not only involve on a local basis but also involves business actors. The competition during the Covid 19 pandemic was no exception, which had a tremendous impact, thus hampering various areas of life. One of the sectors most affected is the economic sector. Competition in the business world as a benchmark in creating better and more valuable products, competition is a developmental stage of a cultural phenomenon that inevitably has to be passed, the most important thing is how to respond and prepare for the face because it is not easy to compete with other products, business actors are challenged to be more competitive strategically by increasing their ability to compete in domestic competition and also increasing their ability to compete professionally, with the right strategy that must be applied to ensure success through exploiting existing opportunities, one of them. The tobacco business is a very promising business, even though there are many challenges, but the tobacco business is able to survive the competition even during the Covid 19 pandemic.Of course, by creating innovations, creative ideas and loyalty to consumers are things that must be prioritized in order to be able to compete with actors. other businesses, in order for the survival of a tobacco business to survive and not be eroded by competition, this business actor has much to deal with, of course by creating solutions to overcome the problem of competition in the business itself, because tobacco is one of the most important agricultural commodities. high value.